Cold water therapies: minimising risks - Tipton, M.; Massey, H.; Mayhew, A.; Morgan, P. (British Journal of Sports Medicine, 2022)
Cold water immersion (CWI) is a `hot topic` at the moment. In many countries, there has been an explosion in the number of individuals undertaking CWI for anecdotally claimed mental and physical health-related benefits.1 These immersions range from static immersions in home-based ice baths and cold showers, to open water swims and dips. Associated with this, in 2021 Her Majesty`s Coastguard in the UK reported a 52% increase in call-outs associated with swimming and dipping and, between 2018 and 2021, there was a 79% increase in open-water swimming deaths (34-61 deaths) in the UK.2